Resilience of Smallholder Palm Oil Farmers in Sidomulyo Village, South Sumatra - Robi'a Al Adawiyah; Aditiya, Rahadiyand; Rizky, Maulana; Humairah; Robby, Syauqi Ridlo (KOMUNITAS, 2024)
The size of agricultural land ownership is a crucial asset for farmers in achieving abundant harvests. Smallholder Palm Oil Plantations are owned by farmers with limited harvest scales. Small farmers often face challenges in meeting their daily needs and acquiring agricultural inputs. This dilemma in the lives of small farmers prompted the researcher to delve deeper into their existence and the strategies they can employ to create economic resilience. This study adopts a qualitative case study approach to investigate the phenomenon in depth. The findings indicate that small farmers owning less than 2 hectares of land need to enhance their capacity to optimize available resources. Additionally, the minimal agricultural yields necessitate the development of new economic sectors and innovations in sustainable agricultural systems.